Hazelnut extract-loaded nanostructured lipid carriers and evaluation of their antioxidant properties - Emanet, Melis; Şen, Özlem; Pignatelli, Francesca; Lavarello, Chiara; Petretto, Andrea; Ciofani, Gianni (Frontiers in Bioengineering and Biotechnology, 2022)
Reactive oxygen species (ROS) are a common hallmark of many degenerative diseases, developing in all those cases where a failure of physiological antioxidant mechanisms occurs (in particular, antioxidant enzymes and the glutathione system), or in case of exposure to an extremely high level of oxidants. In this regard, antioxidant natural extracts are promising compounds as preventive or therapeutic agents against ROS-dependent degenerations. In this study, a deep investigation of hazelnut (Corylus avellana) extract has been performed in terms of mass spectroscopy, evaluation of phenolic content, and antioxidant capacity. Then, nanostructured lipid carriers (NLCs) have been exploited for encapsulation of the hazelnut extracts in order to achieve prolonged bioactivity, increased stability, and targeting through a sustainable delivery approach. The hazelnut extract-loaded NLCs (NE_NLCs) have been deeply characterized for their stability, production yield, and encapsulation efficiency. Moreover, NE_NLCs showed optimal cytocompatibility on human dermal fibroblast (HDF) cells, as well as excellent antioxidant activity, upon pro-oxidant stimulus on HDF cells. This comprehensive study demonstrates the therapeutic potential of the NE_NLCs, that encourages us to promote this approach for further studies.